Programa interventivo para padres y madres adolescentes en sus prácticas de crianza para la formación integral de sus hijos (2022)
This study aims to identify parenting practices, apply the "Crecer felices en Familia" (“Growing up happy as a family”) program and determine the impact after the intervention. Method: It has a quantitative methodology of descriptive scope and quasi-experimental design, made with a population of adolescent mothers and fathers aged between 12 and 19 years old, of 1 and 2 socioeconomic stratum, inhabitants of the human settlement of Guatiguará of the municipality of Piedecuesta - Santander, selecting a non-probabilistic sample of 35 adolescent mothers and fathers.